Preeclampsia, Natural History, Genes, and miRNAs Associated with the Syndrome - Laura Parada-Niño; Luisa Fernanda Castillo-León; Adrien Morel (Journal of Pregnancy)
Preeclampsia (PE) is a hypertensive disease that affects pregnant women after 20 weeks of gestation. This disease is associated with an important risk of maternal and fetal mortality. PE is described as a placental pathology because, after delivery, most women recover normal arterial pressure. Poor invasion of the spiral arteries is a phenomenon well described in PE; this leads to a hypoxic uterine bed and imbalance of antiangiogenic and proangiogenic factors in the uteroplacental region, which in turn triggers the disease phenotype. The causes of the pathology are unclear; nevertheless, numerous approaches, including next-generation sequencing, association, and case control and miRNA studies, have shed light on the genetic/molecular basis of PE. These studies help us better understand the disease to advance new treatment strategies.